Tanggung Jawab PT Nusa Timor Perkasa Sebagai Developer Dalam Penjualan Rumah Melalui Kredit Pemilikan Rumah (KPR) Perumahan Nusa Persada Di Naioni Kota Kupang - Buraen, Stefanus Asa Emuel; Jacob, Yossie M Y; Dinata, Husni Kusuma (Law Faculty, Nusa Cendana University, 2025)
Developers or what are known as housing development companies are companies engaged in housing development from various environmental infrastructure and social facilities needed by their residents. Housing is defined as a residential area equipped with public facilities and supporting infrastructure. Banking plays a role in providing financing facilities through Home Ownership Credit (KPR). KPR is a credit facility provided by banks for customers to buy or renovate a house. In its implementation, developers work with banks to facilitate public access to home ownership. This study discusses (1) the legal relationship of the parties in the sale of a house through Home Ownership Credit and (2) the developer's responsibility for the quality of the house building after the Home Ownership Credit agreement.This study is an empirical legal study with a qualitative descriptive method. The results of the study indicate that the legal relationship between the parties occurs since the signing of the agreement, namely the cooperation agreement between the developer and the bank, the sales and purchase agreement between the developer and the consumer, and the credit agreement between the bank and the consumer in accordance with Article 1320 of the Civil Code. The developer's responsibility is basically to complete the construction of the building, provide infrastructure, provide facilities, provide public utilities, take care of the distribution of certificates, and be responsible for the subsidized housing building after the credit agreement. The principle of responsibility applied by the developer to consumers is the principle of responsibility with limitations (limitation of liability).